Human adipose tissue blood flow and micromanipulation of human subcutaneous blood flow. - Goossens, G; Karpe, F (2008)
Regulation of blood flow in tissues such as skeletal muscle, liver, and adipose tissue is needed to meet the changing local metabolic and physiological demands under varying conditions. In healthy individuals, adipose tissue blood flow (ATBF) is remarkably responsive to meal ingestion, but changes in ATBF in response to other physiological stimuli, such as stress and physical exercise, have also been noted. The ATBF response to nutrient intake may be of particular importance in the regulation of metabolism by facilitating transport of nutrients as well as signaling between adipose tissue and other metabolically active tissues. A reduction in both fasting and postprandial ATBF has been observed in obesity; this impairment is associated with insulin resistance. A better understanding of the physiological basis for (nutritional) regulation of ATBF may therefore give insight to the relationship between disturbances in ATBF and the metabolic disturbances observed in response to insulin resistance. In this chapter, we describe some different approaches to quantify human ATBF, with a particular emphasis on the 133xenon wash-out technique and a method by which regulatory properties of subcutaneous ATBF can be studied by pharmacological micromanipulation (microinfusion).